Induction of genetic variability in phalaenopsis orchids through hybridization and embryo culture - Deepali Rahi (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2017)
The family Orchidaceae has a rich diversity and wide range of adaptation. Orchids are known to be present in all continents except Antartica. Among all orchids, Phalaenopsis the ‘moth orchid’ is eminent for the availability in a variety of color, shape, size and pattern in its hybrids. Hence, it is gaining more attention from a trade point of view. However, the current trend of importing these hybrids from countries like Singapore, Thailand and Malaysia shows that Phalaenopsis breeding has yet to attain its pinnacle to fulfil the rapidly enhancing demand. This demand can be met by extensive hybridization combined with rapid micropropagation technique with which orchids can be grown at a faster rate. As more and more hybrids are developed, there is a need of a tool to detect the genetic relationship between existing cultivars as well as novel hybrids. ISSR molecular marker system is PCR based, dominant marker and has proved to be a strong tool to distinguish between the varieties at the molecular level. Keeping these points in view the study was undertaken so as to analyze the genetic relationship between parents of Phalaenopsis which exhibit variability at phenotypic level and develop hybrids by hybridization and embryo culture. Six Phalaenopsis varieties namely Elegant Yellow, Elegant Purple, Elegant Fairy, Pink, Violet and Winter Spot were selected for the study. The parents were assessed with respect to morphological characters of leaf, shoot and flowers, floral biology and genetic relationship prior to hybridization. Among the morphological characters studied Phalaenopsis parents varied significantly with respect to total number of leaves, leaf area, and shoot height. Statistical analysis showed that varieties varied significantly for floral characters i.e number of days from first flower opening to last flower opening, days for wilting of the first flower, days for wilting of the last flower, flower size, spike length. Flower size was observed to be biggest in Winter Spot and smallest in Elegant Yellow. Flowers of six selected varieties bloomed between the month of March to November. All varieties bloomed once in a year except Winter Spot which came to flowering twice in a year. Dendrogram generated based on phenotypic characters grouped the selected varieties into different clusters between similarity coefficient of 0.10 to 1.00. At 20 per cent similarity coefficient bifurcation occurred which showed that all the varieties were distinctly variable from each other and shared only 20 per cent similarity. Anthesis time of the flowers ranged from 5:00 am to 2:00 pm among the varieties. Elegant Yellow opened earliest of all (5:00 am -8:00 am) whereas Violet was observed to open from 11:00 am - 2:00 pm. Maximum number of days for stigma receptivity was observed in Winter Spot (3-12 days) and Violet had minimum (1-5 days). Palynology results of parents revealed that there were no significant difference between varieties for pollen fertility percentage, length of pollen tube and pollen production per pollinium. Whereas significant difference was observed in pollen germination percentage and pollen diameter. Pollen germination percentage was maximum (100 %) in Elegant Yellow and minimum in Elegant Purple (47.2%). Pollen diameter was maximum in Winter Spot (107.68 μ) and minimum in Pink (84.58 μ). Out of 13 ISSR primers screened, seven primers gave maximum number of clear and reproducible bands. 100 per cent polymorphism was obtained by UBC 841. Dendrogram generated based on molecular data clustering had similarity coefficient between 0.56-0.78. Three different clusters were observed in which Elegant Purple and Pink were most closely (78 %) related to each other. Inter varietal crosses made in all possible cross combinations between the selected varieties resulted in pod set of six crosses. They were Winter Spot X Elegant Purple, Winter Spot X Pink, Elegant Purple X Pink, Pink X Winter Spot, Pink X Elegant Purple and Violet X Elegant Purple. Pod set percentage ranged between 0 – 66.6 per cent among the varieties. Embryo culture was done with seeds from successful crosses in MS and Knudson-C basal media with and without growth regulators. Seeds from the crosses Winter Spot X Pink, Elegant Purple X Pink and Pink X Elegant Purple germinated maximum (50 %) in half MS medium supplemented with 1 mg l-1 BA, 0.1 mg l-1 NAA and 0.5 per cent activated charcoal and in Knudson-C (40 %) basal medium supplemented with BA 3 mg l-1 and NAA 0.3 mg l-1.Germinated seeds developed into protocorms in the crosses between Pink × Elegant Purple and Elegant Purple × Pink. Protocorms when sub cultured to half MS basal medium supplemented with 1 mg l-1 each of BA and NAA exhibited leaf differentiation from the cross Pink × Elegant Purple. Therefore, plantlets emerging from these crosses have to be further grown for assessing the genetic and phenotypic variability generated.